Evidence for Thermal‐Based Transition in Super‐Lattice Phase Change Memory (Phys. Status Solidi RRL 4/2019). Issue 4 (11th April 2019) - Boniardi, Mattia; Boschker, Jos E.; Momand, Jamo; Kooi, Bart J.; Redaelli, Andrea; Calarco, Raffaella
Abstract : A reduction of the SET and RESET currents by more than 60% with respect to conventional GeTe‐Sb2 Te3 (GST) alloys is demonstrated by using Phase Change Memory (PCM) cells containing (GeTe‐Sb2 Te3 )/Sb2 Te3 Super‐Lattices (SLs), see article no.1800634 by Mattia Boniardi et al. Moreover, the authors' SL PCM devices feature similar characteristics in terms of the memory transition as conventional memory cells based on GST, even though showing reduced power consumption, indicative of an efficiency augmented SET‐to‐RESET transition. The reduced power consumption is attributed to an increased thermal resistance of the SL stack with respect to the bulk GST alloy.